Impact of Internet Integrated Financial Education on Students’ Financial Awareness and Financial Behavior - Liu, Hong-Cheng; Lin, Jie-Shin (Frontiers in Psychology, 2021)
In daily life, most people engage in money-related behavior. Adequate financial knowledge is required to successfully manage tasks such as daily expenditure and the transformation of assets or debts, small or large. However, the extent of financial knowledge may vary between individuals. With inadequate financial knowledge, people may easily fall into financial difficulties without having sufficient knowledge to redress them. A total of 217 students from departments of finance in universities in Fujian completed an 18-week educational course delivered via the Internet on integrated financial education (5 hours per week for a total of 90 hours). The conclusions were as follows: 1. The Internet can be used to provide education on making ends meet, cutting costs, and increasing profits. It is suitable for beginner students and new graduates who are rapidly accumulating money management experience. 2. Knowledge provided in the course includes the causes of investment, comprehensive changes in the market, unexpected risks, and wrong decision-making. As such, education provided through the Internet can assist in the teaching of money management and investment. 3. Providing teaching on integrated financial education through the Internet avoids the pitfalls of getting lost in the real-world investment market. We expected to cultivate students’ finance-related knowledge, skills, and attitudes through internalization of the financial literacy of money management.